A Framework For Chili Fruits Maturity Estimation Using Deep Convolutional Neural Network - Zainuddin, Muhammad Noorazlan Shah; Mohd Hussin, Najihah; Ahmad Radzi, Syafeeza; Mohd Saad, Wira Hidayat; Mohd Noh, Zarina; Sulaiman, Noor Asyikin; Razak, M. S.J.A. (Wydawnictwo SIGMA-NOT, 2021)
An agriculture robot has been demanded in recent years. Inaccurate in estimating the maturity of the chili always happens since the human eyes are tend to prone to errors. Serving an effective, innovative, feasible chili recognition system would help farmers as economical alternative by reducing the workloads while increasing fruit yield. Hence, a comprehensive framework of chili maturity estimation using deep learning is carried out.